In-vitro antifungal activity of Vernonia amygdalina against Botrytis cinerea in tomato - Yusoff, Siti Fairuz; Tengku Muda Mohamed, Mahmud; Haron, Farah Farhanah; Ismail, Siti Izera; Sakimin, Siti Zaharah (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
Grey mold disease caused by Botrytis cinerea is the most severe disease in tomato and known to be a limiting factor in tomato production worldwide. Synthetic fungicide is widely used to control this pathogen. However, it posed detrimental effects to the environment and human health as well as increasing resistance in B. cinerea. Vernonia amygdalina leaf extracts possess antifungal properties that are useful for the development of safer alternatives. Therefore, the aim of this study was to evaluate in-vitro antifungal activities of V. amygdalina extract against B. cinerea in tomato. The powdered leaves of V. amygdalina were sequentially extracted with organic solvents; (1) hexane, (2) dicholoromethane, (3) methanol, and water. In vitro antifungal test was conducted using poison agar technique. Among the crude extract, the effectiveness against B. cinerea as follows, dichloromethane > methanol > aqueous > hexane. Dichoromethane crude extract shown highly significant in PIRG and the antifungal activities were increased with the increasing of concentration level. The SEM observation proved that the treatment might alter the fungus morphology which lead to fungal growth inhibition.